The global movement towards a public health approach to substance use disorders - Kimberly Johnson; Irina Pinchuk; Marie Isabel E. Melgar; Martin Osayande Agwogie; Fernando Salazar Silva (Annals of Medicine, 2022)
Drug misuse is a global problem. Markets that supply illegal drugs often span international borders. However, each country has different primary drugs of use, populations that are using and consequences of use. The policy approach of each country to addressing substance use disorders can be characterized along a continuum between purely public health approaches and purely law enforcement approaches. Historically, a law enforcement approach has been the primary strategy in much of the world. However, there is a growing movement towards use of a public health approach. This article provides four case examples, Ukraine, Philippines, Nigeria and Peru, where there is movement to develop addiction public health infrastructure. The work varies by country, but includes regulatory changes, workforce development and resource allocation all of which are supported by the United Nations Office on Drugs and Crime (UNODC) and multi-national organizations that provide training and technical assistance, funded primarily by the European Union and United States governments. All four countries highlighted have barriers to moving towards a more public health approach which may include popularity of the law enforcement approach, turbulent government environments, and economics of being a drug producing nation. However, whether starting from the top down with changed policies, such as Ukraine or from the bottom up with training community members as in the Philippines, each country provides an example of how donor resources can be applied to make the transition towards a more humane and evidence-based approach to addressing substance use disorders.Key MessagesWhile the primary approach to addressing drug use has focussed resources on law enforcement for over 100 years, many countries are adopting elements of a public health approach including prevention and treatment of the harms of drug use including substance use disorders.There is a growing global movement to make policy towards drugs and drug users more humane and evidence-based.Donor nation resources can be applied in a variety of combinations to improve care and outcomes for people who use drugs in low- and middle-income countries.